Behavioral Analyses of GHB: Receptor Mechanisms - Carter, Lawrence P. (2008)
GHB is used therapeutically and recreationally, although the precise mechanism of action responsible for its different behavioral effects is not entirely clear. The purpose of this review is to summarize how behavioral procedures, especially drug discrimination procedures, have been used to study the mechanism of action of GHB. More specifically, we will review several different drug discrimination procedures and discuss how they have been used to qualitatively and quantitatively study different components of the complex mechanism of action of GHB. A growing number of studies have provided evidence that the behavioral effects of GHB are mediated predominantly by GABA(B) receptors. However, there is also evidence that the mechanisms mediating the effects of GHB and the prototypical GABA(B) receptor agonist baclofen are not identical, and that other mechanisms such as GHB receptors and subtypes of GABA(A) and GABA(B) receptors might contribute to the effects of GHB. These findings are consistent with the different behavioral profile, abuse liability, and therapeutic indications of GHB and baclofen. A better understanding of the similarities and differences between GHB and baclofen, as well as the pharmacological mechanisms of action underlying the recreational and therapeutic effects of GHB, could lead to more effective medications with fewer adverse effects.